2011
DOI: 10.3390/md9091554
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and α-Glucosidase Inhibitory Mechanisms of Bis(2,3-dibromo-4,5-dihydroxybenzyl) Ether, a Potential Marine Bromophenol α-Glucosidase Inhibitor

Abstract: Bis(2,3-dibromo-4,5-dihydroxybenzyl) ether (BDDE), derived from the marine algae, is a potential α-glucosidase inhibitor for type 2 diabetes treatment. In the present study, a synthetic route was established as a valid approach to obtain BDDE. Fluorescence spectra, circular dichroism spectra and molecular docking methods were employed to elucidate the inhibitory mechanisms of BDDE against α-glucosidase. The results showed that BDDE could be prepared effectively and efficiently with the established synthetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 29 publications
8
40
0
Order By: Relevance
“…As previous studies have suggested that the helix structure could be stabilized by targeting compounds with polyhydroxyl groups, 21, 23, 49 our CD results suggest that the helix structures were reduced with increasing concentrations of GA, MF, and MJ. Therefore, this implied that binding site 3 is not targeted by these GCGs.…”
Section: Resultssupporting
confidence: 74%
“…As previous studies have suggested that the helix structure could be stabilized by targeting compounds with polyhydroxyl groups, 21, 23, 49 our CD results suggest that the helix structures were reduced with increasing concentrations of GA, MF, and MJ. Therefore, this implied that binding site 3 is not targeted by these GCGs.…”
Section: Resultssupporting
confidence: 74%
“…Alpha-glucosidase, another candidate involved in carbohydrate synthesis and breakdown, have role in diabetes, viral infection and, even cancer. Acarbose, voglibose, and miglitol are clinically used anti-diabetic agents, which suppresses the α-glucosidase activity (Liu et al, 2011). The results of the study displayed that next to untreated sample (43.03 %), pre-treatment by dry heat at 100 C for 10 min followed by hexane extracted oil shows highest (42.42 %) inhibition during α-amylase inhibition assay, whereas microwaved samples displayed the minimum activity (17.20 %) (Fig.…”
Section: Peroxide and Acid Valuesmentioning
confidence: 86%
“…People have followed different extraction techniques to recover vegetable oil (Febrianto and Yang, 2011), but still more detailed research is needed to increase the quality and quantity of the product. Even though previous literatures (Jung et al, 2012;Li et al, 2014) are available about perilla oil extraction, there is no adequate information about the pre-treatment methods and their effect on extraction yield, quality of seed oil, bioactive compounds and bioactivities of the perilla seed oil. Since the extraction procedure for obtaining perilla seed oil should not compromise any features of its natural medicinal traits, the current study was conducted to compare the different pre-treatment techniques followed by hexane extraction for perilla seed oil and to evaluate the anti-diabetic properties of extracts.…”
Section: Introductionmentioning
confidence: 99%
“…This finding might come from the chemical properties of RA derivatives and the different affinities and interactions of these chemicals to α‐glucosidases from different origins with different mechanism for α‐glucosidase inhibitory activity (mammalian, bacteria, or yeast α‐glucosidase). In previous reports, we found evidence that phenolic hydroxyl groups are critical for α‐glucosidase inhibitory activities (Liu, Zhang, Wei, & Lin, ; Shen et al, ), which might be from hydrogen bonding of the hydroxyl group with aromatic rings in α‐glucosidase.…”
Section: Resultsmentioning
confidence: 63%